"Will you tell me the ways you’ve been keeping beautiful to stay alive?": Correspondence between Orlando and Leòn - Ochoa, Orlando; Ozuna, León (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Orlando Ochoa and León Ozuna write to each other and reflect on the details of their friendship, love, loneliness, and sex across distance. This epistolary/poetic exchange is an answer to the question of how Ochoa and Ozuna—Mexican poets and lovers from the Rio Grande Valley of South Texas—keep alive in the world.